Using Visual Arts Education in Dermatology to Benefit Resident Wellness and Clinical Communication - Anusha M. Kumar; Gun Ho Lee; Laurel A. Stevens; Bernice Y. Kwong; Kristin M. Nord; Elizabeth E. Bailey (Association of American Medical Colleges, 2021)
Introduction Art education interventions improve observation skills among dermatology residents, but there is limited data regarding their benefits to wellness and clinical communication. Methods Residents in the Stanford dermatology residency program participated in an arts-based education session, repeated in the fall of 2018 and 2019, that included a rotation of observational exercises adapted from the Artful Thinking program through Harvard Project Zero. The 2018 session featured exercises on identification and understanding of visual observation, while the 2019 session featured exercises on perspectives and objectivity of visual observation. Participants completed preintervention, postintervention, and 3-month follow-up surveys in fall 2018 and a postintervention survey in fall 2019. Results Twenty-one residents participated in the 2018 education session and produced an adequate response rate (62%-90%) across surveys. At 3 months, five of 13 residents (39%) reported new use of art for mindfulness and stress reduction, 12 of 13 (92%) could recall an example of use of observation to improve patient communication, and four of 13 (31%) confirmed and described adjustments to their handoff technique. In 2019, 13 out of 18 participants (72%) completed the postintervention survey. Responses reinforced themes from the prior iteration but focused on perspective, objectivity, context, and uncertainty in observations. Respondents also identified additional arenas of communication to benefit from these observational techniques. Discussion Dermatology residents increased use of art for personal wellness and adjusted clinical communication strategies after a single arts-based education session. Annual repetition with novel exercises maintained engagement and yielded additional participant insights.